2011
DOI: 10.1245/s10434-011-1706-3
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Survival after Surgical Treatment for Melanoma

Abstract: Background Surgical-treatment outcomes for melanoma in African Americans are poorly characterized due to low incidence of melanoma among African Americans. We examined differences by race in overall and melanoma-specific survival, stratified by receipt of surgical treatment and by specific types of surgical treatment. Methods Data from the 1973–2004 public-use Surveillance, Epidemiology and End Results (SEER) Program were analyzed using Cox proportional hazard models to compare the effects of surgical treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 42 publications
1
77
0
Order By: Relevance
“…Similar risk-adjusted models have since demonstrated that non-white race is an independent predictor for increased post-operative mortality following congenital heart disease operations[1]. Recent adult surgical literature has also implicated race as a predictor of post-operative morbidity, mortality, and increased length of stay[10, 2123]. Collectively, these data support consideration of race in both risk stratification and healthcare reform aimed at the elimination of disparity within the care of children.…”
Section: Discussionmentioning
confidence: 95%
“…Similar risk-adjusted models have since demonstrated that non-white race is an independent predictor for increased post-operative mortality following congenital heart disease operations[1]. Recent adult surgical literature has also implicated race as a predictor of post-operative morbidity, mortality, and increased length of stay[10, 2123]. Collectively, these data support consideration of race in both risk stratification and healthcare reform aimed at the elimination of disparity within the care of children.…”
Section: Discussionmentioning
confidence: 95%
“…The Table illustrates our current knowledge on this topic organized along the cancer continuum. 24,613,27,29,33,37,38,40,4655,5962,65,68,70,71,73,74 …”
Section: Gaps In Knowledgementioning
confidence: 99%
“…4 Evidence also suggests variability in the quality of care received by minority patients with cutaneous melanoma. A Surveillance, Epidemiology, and End Results–based study found that blacks were less likely than Caucasians to receive surgical treatment for melanoma, 13 and those who underwent surgery experienced shorter survival time than other races. 13 …”
Section: Introductionmentioning
confidence: 99%
“…This disproportion is mainly attributed to the substantially higher risk of melanoma in this racial group [2]; however, emerging evidence suggests that non-White racial groups are more likely to experience unfavorable prognoses despite their lower incidence [27]. Large-scale studies on the population of the United States generally, and of California, New York, Connecticut, and Florida specifically, identified socioeconomic and racial disparities in association with melanoma [7, 8, 12, 27-36]. Most of these studies used cancer registry records and the Surveillance, Epidemiology, and End Results (SEER) database.…”
Section: Introductionmentioning
confidence: 99%